DAMPAK PENGGUANAAN DIGITAL MARKETING TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN COFFEE SHOP DI BANDAR LAMPUNG: DAMPAK PENGGUANAAN DIGITAL MARKETING TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN COFFEE SHOP DI BANDAR LAMPUNG - Rizal, Ade; Damayanti, Damayanti; Nugeraha, Prasetya (Jurnal Kompetitif Bisnis, 2023)
In the world of business competition, purchasing decisions become one of the important factors that must be considered by business players. In a technology-driven world today, social networking sites have become a pathway through which retailers can expand their marketing to a wider range of consumers. This research aims to determine the influential of digital marketing on consumer purchasing decisions of coffee shops in Bandar Lampung. The population of the study is the consumers of coffee shops in Bandar Lampung. This study uses explanatory research with a quantitative approach. The population of this research is the consumers of coffee shops in Bandar Lampung. The sampling technique used is accidental sampling and nonprobability sampling method with a sample size of 100 respondents. Data was collected using a questionnaire. The analysis techniques used include validity test, reliability test, simple linear regression, t-test, and R2 test using SPSS 26.0 as the tools. The results of this research indicate that the digital marketing variable has a significant influential on consumer purchasing decisions of coffee shops in Bandar Lampung.